TINJAUAN KRITIS NILAI-NILAIPENDIDIKAN KARAKTER SEBAGAI MEDIA PENDIDIKAN POLITIK BAGI KADER PARPOL - Hasnan Hanif (Pascasarjana IAIN Sorong, 2018)
The main pillar of political civilization is political party. If the political party was weak accordingly political civilization would be fragile too. The cause of political party cannot be the main pillar of political civilization was less educated society politically. The character values which become medium in political education are as follows: Religious, honest, toleration, discipline, work hard, creative, stand by their feet, democratic, willingness, spirit of nation, love nation, achievement of appreciation, friendly, love peace and fond of reading, care of environment, social care and responsibility the form source of character values are religious, the five of Principles and culture. The last the character values as a medium of political education will form the understanding of political character, political affection political wise and political prophetic. The character values will make come true of religious political civilization in Indonesia.